Integrating impacts on climate change and biodiversity from forest harvest in Norway. (June 2018) - Iordan, Cristina Maria; Verones, Francesca; Cherubini, Francesco
Abstract: Forest ecosystems provide a variety of services, from climate regulation to biodiversity conservation. Temporary land cover variations such as those related to forest management can contribute to climate change through both biogeochemical (carbon, warming) and biophysical (albedo, cooling) mechanisms. As global rising demand for biomass for energy and materials can contribute to biodiversity losses, there is an evident need for integrated assessments of climate and biodiversity impacts to investigate possible trade-offs and synergies. We explore the integration of impacts on climate change and biodiversity from forest harvest for three case studies based on forest plantations in Norway. We focus on impacts from land disturbance after clear-cutting using three plots of one ha each of homogeneous forest in two ecoregions in Norway involving three different tree species: spruce, pine and birch. We use existing ecoregion specific characterization factors (CFs) to quantify occupation, short-term and long-term transformation impacts of land use on biodiversity loss for five taxonomic groups: mammals, birds, amphibians, reptiles and plants at regional and global level. For climate change impacts, we quantify the contributions of CO2 fluxes and changes in albedo. We estimate CFs for two complementary climate metrics, namely global warming potential (GWP) and global temperature change potential (GTP) for time horizons of 20 and 100 years and quantify impacts in CO2 equivalents. We pursue the integration of impacts on climate and biodiversity from a time perspective: very short (GWP20 and land occupation), medium (GWP100 and land transformation within 100 years) and long (GTP100 and land transformation after 100 years). We find CFs from −0.21 to 1.6 kg CO2 -eq./kg CO2 for carbon emissions, and from −0.03 to −1.4 kg CO2 -eq./kg CO2 for albedo changes, while net characterized impacts range from −44.8 t CO2 -eq./ha (GTP100, spruce) to 93.25 t CO2 -eq./ha (GWP20, spruce). Damages to biodiversity range from 4.76 * 10 −13 to 6.24 * 10 −8 global species eq. lost per ton of carbon harvested. Our results reinforce the notion that spatially and temporally explicit analyses are vital when assessing life-cycle impacts from land derived products. We show that the existing set of multiple and complementary indicators for climate change and biodiversity impacts can be integrated into a common framework to better inform about the complex heterogeneities of the forest ecosystem response to disturbances. We argue for a more frequent consideration of integrated impacts on biodiversity and climate change from forestry operations to better highlight possible co-benefits or adverse side-effects of forest management strategies.